Numerical modeling and experimental validation of fluid flow in micro- and meso-fluidic siphons - Akhras, Nour; Singh, Gurjas; Gill, Kirandeep K.; Bola, Shaan; Al-Hakeem, Kareem; Reis, Nuno M. (Frontiers in Chemical Engineering, 2024)
Siphons have been used for thousands of years to transfer fluids without the use of pumps or power and are present in our daily lives. Paradoxically, only in recent decades has the operation of a siphon been fully clarified, which is now understood to be exclusively linked to gravity and molecular cohesion. Siphons are uniquely able to offer automatic, intermittent flow, yet present the main drawback of requiring a source of energy to induce initial flow. Our research team has recently disclosed a microfluidic siphon able to self-prime and deliver a sequence of bioanalytical reagents, previously demonstrated for high-performance, multi-reagents diagnostic testing. Here we show for the first time 2D and 3D Computational Fluid Dynamics (CFD) modelling and experimental characterization of fluid flow in a range of miniaturised hydrophilic siphons of varying hydraulic liquid height to length ratios, H/LT = 0-0.9 using fluids of varying viscosities. CFD simulations using velocity-driven and pressure-driven inlet boundary conditions were in general in good agreement with experimental fluid flow rates and pressure-balance predictions for plastic 0.2 mm and glass 0.6 mm internal diameter microfluidic siphons. CFD predictions of fluid flow in ‘meso-scale’ siphons with 1 mm and 2 mm internal diameter also fully matched normalized experimental data suggesting miniaturized siphons are scalable, with discharge rate and pressure drop readily predicted and fine-tunable through physical properties of the fluid and few design parameters of the siphon. The wide range of experimental and numerical parameters studied here provide an important framework for the design and application of gravity-driven micro- and meso-fluidic siphons in many applications, including but not limited to life sciences, clinical diagnostics, and process intensification.